Reality TV consumption patterns: An exploration among Malaysian viewers - Shamshudeen, Rosya Izyanie; Bolong, Jusang; Razali, Asbah; Syed, Md Azalanshah Md; Zulkifle, Nor Fazura Md (Faculty of Social and Political Science, Universitas Airlangga, 2025)
This study focuses on the viewership behaviour patterns, motivations for viewership, viewership preference for reality TV programmes, and perceptions of reality TV based on demographic aspects. It examined the consumption of reality TV programmes among Malaysian society through quantitative method research. This involved the use of the survey based on a questionnaire as the instrument for the data collection. This study distributed questionnaires among 400 Malaysian respondents and findings show that reality TV has a very high viewership among the Malaysian population. This is due to the fact that Malaysian viewers find the programmes very relatable and entertaining. The reality TV programme featured in the survey also attracted strong viewership among respondents. Female respondents in Malaysia were found to watch reality TV programmes more frequently than males. This research provides insights into the consumption patterns among multi-ethnic Malaysians, including insights into viewing behaviours, perceived realism, motivations for watching, connectedness to the content, and the influence of gender and age on these aspects.